2014
DOI: 10.1371/journal.pone.0105395
|View full text |Cite|
|
Sign up to set email alerts
|

Recombination Blurs Phylogenetic Groups Routine Assignment in Escherichia coli: Setting the Record Straight

Abstract: The characterization of population structures plays a main role for understanding outbreaks and the dynamics of bacterial spreading. In Escherichia coli, the widely used combination of multiplex-PCR scheme together with goeBURST has some limitations. The purpose of this study is to show that the combination of different phylogenetic approaches based on concatenated sequences of MLST genes results in a more precise assignment of E. coli phylogenetic groups, complete understanding of population structure and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Recombinant sequences have been known for a long time to strongly distort phylogenies because they merge independent evolutionary histories into a single lineage. Recombination erodes the phylogenetic signal and misleads classic treeing algorithms, which assume a single underlying history (Didelot and Maiden, 2010;Martin, 2009;Pease and Hahn, 2013;Posada and Crandall, 2002;Schierup and Hein, 2000;Turrientes et al, 2014). Hence, the first filtering step in the pipeline is the detection of putative recombinant sequences using the very fast, sensitive and robust phi(w) statistic (Bruen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant sequences have been known for a long time to strongly distort phylogenies because they merge independent evolutionary histories into a single lineage. Recombination erodes the phylogenetic signal and misleads classic treeing algorithms, which assume a single underlying history (Didelot and Maiden, 2010;Martin, 2009;Pease and Hahn, 2013;Posada and Crandall, 2002;Schierup and Hein, 2000;Turrientes et al, 2014). Hence, the first filtering step in the pipeline is the detection of putative recombinant sequences using the very fast, sensitive and robust phi(w) statistic (Bruen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…An updated multiplex PCR method was more recently devised by Doumith et al (19). An independent study by Turrientes et al subsequently compared both methods against a multi-locus sequence typing standard and demonstrated superiority of Doumith's method with regards to accuracy of phylogroup assignment (20).…”
Section: Expec Lineage Determination; a Brief Historymentioning
confidence: 99%
“…In order to maintain the comparability of the results obtained during the years 2008-2014, we decided not to replace the multiplex-PCR scheme used by the novel multiplex-PCR scheme of Clermont et al (2013). Moreover, the assignment of the phylogroups obtained with the protocol of Doumith et al (2012) already showed a better correlation to the MLST types than the protocol of Clermont et al (2013) and, therefore, has been also recommended as the protocol of choice for the phylotyping (Turrientes et al, 2014).…”
Section: Confirmatory Tests For Esbl-producing Isolates Additional Amentioning
confidence: 99%